AMBIENTE, SAÚDE E QUALIDADE DE VIDA: VIVENCIANDO EXPERIÊNCIAS DE ENSINO-APRENDIZAGEM ATRAVÉS DA EXTENSÃO - Oliveira, Rosemeri M. d.; Bianchi, Vidica; Almeida, Maris L. (Salão do Conhecimento, 2013)
Resumo